Shallow Megathrust Slip During Large Earthquakes That Have High P Coda Levels. Issue 1 (13th January 2020) - Wu, Zhenbo; Lay, Thorne; Ye, Lingling
Abstract: Determining the up‐dip extent of slip during large megathrust earthquakes is important for understanding tsunami generation, potential for subsequent failure of the shallow megathrust, and plate contact depth‐varying frictional properties. Recent measurements of early P coda amplitudes relative to direct P signals for the period range 7 to 15 s find high P coda / P ratios for many events with finite‐fault rupture models that have slip extending to near deep trenches, resulting in enhanced pwP (water‐reverberation) generation. However, some events with high P coda / P measures have finite‐fault model solutions that vary in, or lack, shallow slip. We reexamine six large megathrust earthquakes with unexplained high P coda / P ratios (30 July 1995 Chile, M W 8.0; 17 November 2003 Aleutian, M W 7.7; 12 November 1996 Peru, M W 7.7; 7 October 2009 Vanuatu, M W 7.6; 5 May 2015 Papua New Guinea, M W 7.5; and 5 March 2002 Mindanao, M W 7.5), inverting for slip models with depth‐varying dip and varying bathymetry, adjusting kinematic parameters to better allow for the possibility of late shallow slip with associated strong pwP excitation. We confirm that modest patchy late shallow slip (~1 to 3 m) occurred near the trench for the 1995 and 2003 events, accounting for observed high P coda levels and minor tsunamis. The 2009 event appears to have minor shallow slip, whereas the 1996, 2002, and 2015 events do not; their coda amplitudes are likely enhanced by early aftershocks. Refined modeling of the later stages of large megathrust ruptures, guided by P coda levels, improves resolution of the up‐dip limit of co‐seismic slip. Key Points: The estimated up‐dip extent of slip during large megathrust earthquakes from finite‐fault inversions often differs due to parameterization Modeling late P wave and early P coda signals produced by deep water reverberations ( pwP ) improves late/triggered shallow slip resolution Several events with large P coda levels are shown to have late shallow slip; deeper early aftershocks produce strong P coda for other events